The Alexander Technique and Contemporary Dance: An Interview between Marsha and Robert Barsky (AmeriQuests, 2010)
The Alexander Technique, based on the writings and teachings of F. M. Alexander, is a process of learning how to move with more ease, freedom, efficiency, support and balance. The technique encourages reliable integration and coordination of the mental, physical, emotional and spiritual spheres, by awakening and refining sensory awareness. It promotes a deep understanding to the means whereby we respond to stimuli, thus fostering a harmonious relationship to Self. The essence of the Alexander Technique is movement, and as the process of learning and understanding the technique unfolds, the potential for free and unfettered movement is experienced in the entire being. Modern dancers, in particular might be drawn to the Alexander Technique since the very nature and origins of modern dance deal with the freedom of self- expression in motion. Modern dancers are adept negotiators of the body, and in their work they explore a whole range of movements and facets of moving. Through diligent exploration of finely sophisticated movement patterns, a dancer’s kinesthetic sense is, -- through Alexander work, -- sharpened, refined and developed to permit the mover to perceive and convey the subtlest movement shifts.
Keywords: Alexander Technique; F. M. Alexander; pedagogy; modern dance; somatics